2013
DOI: 10.1155/2013/401723
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Type 2 Diabetic Rodent Models

Abstract: Diabetes mellitus, especially type 2 diabetes (T2DM), is one of the most common chronic diseases and continues to increase in numbers with large proportion of health care budget being used. Many animal models have been established in order to investigate the mechanisms and pathophysiologic progress of T2DM and find effective treatments for its complications. On the basis of their strains, features, advantages, and disadvantages, various types of animal models of T2DM can be divided into spontaneously diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 78 publications
0
43
0
3
Order By: Relevance
“…In addition, we measured levels of miR-7a in islets of diabetic models (db/db mice on BKS background), which developed age-dependent hyperglycemia and reduced plasma insulin levels due to β cell dysfunction (Supplemental Figure 5, D-F). In fact, the natural history of the BKS db/db phenotype makes this mouse a faithful model of human obesity and β cell failure leading to overt T2D (29,30). Our analysis revealed that miR-7a levels were decreased by approximately 50% in compensating islets of HFDfed and ob/ob mice ( Figure 6A).…”
Section: Introductionmentioning
confidence: 83%
“…In addition, we measured levels of miR-7a in islets of diabetic models (db/db mice on BKS background), which developed age-dependent hyperglycemia and reduced plasma insulin levels due to β cell dysfunction (Supplemental Figure 5, D-F). In fact, the natural history of the BKS db/db phenotype makes this mouse a faithful model of human obesity and β cell failure leading to overt T2D (29,30). Our analysis revealed that miR-7a levels were decreased by approximately 50% in compensating islets of HFDfed and ob/ob mice ( Figure 6A).…”
Section: Introductionmentioning
confidence: 83%
“…Various genetic, diet and chemically induced diabetic rodent models are utilized to study T2D 1113 . However, these models are accompanied by obesity and do not accurately mimic the lean T2D phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…49 KK faresinde 2-5 aylık yaşa kadar obezitenin şiddeti giderek artmakta ve hiperfaji, hiperinsüli-nemi, İD görülmektedir. 20,67 Pankreatik adacıkların sayısının ve büyüklüğünün artması ile ilişkili olan hiperinsülinemi tablosu, İD'yi kompanse etmekte ve kan glukozunu normal seviyelerde tutmaktadır. 53 İD ve hiperinsülinemi yaklaşık 5. ayda en yüksek değere ulaşmaktadır.…”
Section: Poligenik Modellerunclassified
“…53 İD ve hiperinsülinemi yaklaşık 5. ayda en yüksek değere ulaşmaktadır. 67 KK/A y (Yellow KK obez) farelerde şiddetli obezite, hiperglisemi, hiperinsülinemi, glukoz intoleransı tablosu 8 haftalık yaşta ortaya çıkmaktadır. 67 Genç erkeklerde hiperfaji ve obezite, dişilere göre daha belirgindir.…”
Section: Poligenik Modellerunclassified
See 1 more Smart Citation